Improving energy efficiency in Moroccan homes: Thermal performance of gypsum plaster and expanded clay - Omari, Soufian; Laaroussi, Najma; Ettahir, Aziz (Edelweiss Applied Science and Technology, 2025)
Thermophysical properties of construction materials, such as thermal conductivity and thermal diffusivity, play a crucial role in evaluating the thermal performance of buildings. This study investigates these properties in gypsum plaster mixed with expanded clay granules and assesses its impact on residential building energy demand. Gypsum plaster samples were prepared with varying mass proportions of expanded clay while maintaining a constant water-to-plaster ratio. Thermal conductivity and diffusivity were measured using the heated plate and flash methods, respectively. Additionally, a Trnsys-based simulation was conducted to evaluate the effect of these mixtures on energy consumption. The results indicate that adding expanded clay granules reduces the thermal properties of gypsum plaster, likely due to water absorption during mixing. However, using gypsum plaster with 6% expanded clay led to an 18.16% energy gain. Moreover, insulation of exterior walls and roofs improved energy performance by 21.83% and 33.21%, respectively, while floor insulation negatively affected efficiency. These findings emphasize the importance of material selection in optimizing energy consumption. The study highlights the potential of integrating expanded clay in gypsum plaster to enhance building energy efficiency, offering valuable insights into sustainable construction practices.